1993
DOI: 10.1159/000187289
|View full text |Cite
|
Sign up to set email alerts
|

Renal Toxicity Mediated by Continuous Infusion of Recombinant lnterleukin-2

Abstract: Interleukin-2 (IL-2), a potent lymphokine with antitumoral activity, was used in continuous intravenous infusion for 5 days (18,000,000 IU/m2/day) in 9 treatment cycles in 5 patients with metastatic colorectal carcinoma. During the infusion, patients received agressive fluid replacement titrated by invasive hemodynamic monitoring, aiming at a stable central volemia. Body weight went up an average of 4.5 kg in 5 days, mean arterial blood pressure dropped slightly from day 1 to day 5 (105.4 ± 11.6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Prerenal as well as intrinsic renal lesions have been proposed [11,12,15,18,19]. The kidneys are susceptible to vascular leak [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prerenal as well as intrinsic renal lesions have been proposed [11,12,15,18,19]. The kidneys are susceptible to vascular leak [36].…”
Section: Discussionmentioning
confidence: 99%
“…A case report demonstrated a marked decrease in effective renal plasma flow and creatinine clearance [13]. Two additional studies demonstrated a decrease in creatinine clearance, urinary output and sodium clearance and an increase in urinary N-acetyl-β-D-glucosaminidase activity [18,19].…”
Section: Renal Haemodynamics Sodium and Water Reabsorption During Comentioning
confidence: 98%
“…Prerenal as well as intrinsic renal lesions have been proposed [11,12,15,18,19]. Prerenal as well as intrinsic renal lesions have been proposed [11,12,15,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…non-steroidal antiinflammatory drugs (NSAIDs), vasopressors, volume expanders, diuretics and anti-emetics, which all may have contributed to the observed renal side-effects. Two additional studies demonstrated a decrease in creatinine clearance, urinary output and sodium clearance and an increase in urinary N-acetyl-β-D-glucosaminidase activity [18,19]. It is, however, well recognized that changes in plasma creatinine level and endogenous creatinine clearance are poor predictors of day-to-day changes in renal function [17].…”
Section: Renal Haemodynamics Sodium and Water Reabsorption During Comentioning
confidence: 99%
“…The nephrotoxic effect of OKT3 has been ascribed to transient intragraft T-cell activation and lympholysis, resulting in local production of cytokines that might mediate kidney damage [3.4]. However, the nephrotoxic effect of OKT3 resembles the transient acute renal failure seen in patients receiving recombinant interleukin 2 (IL-2) immunotherapy [7]. This makes it likely that circulating factors are responsible for the nephrotoxicity seen in these patient groups.…”
Section: Introductionmentioning
confidence: 99%